Corporate Social Responsibility (CSR) in the gastronomic sector and its contribution to sustainable tourism development: A case study of the city of Portoviejo - Zamora Herrera, Génesis Jamileth (2026)
This article analyzes the implementation of Corporate Social Responsibility (CSR) practices in gastronomic establishments in the canton of Portoviejo, considering their role as a key component of sustainable tourism development. The research is justified by the need to strengthen the sustainability and competitiveness of the local gastronomic sector, which is affected by informality and limited adoption of responsible practices. A mixed descriptive approach was applied, using semi-structured interviews with 12 restaurant owners, surveys of 384 community members –including employees and customers– and a documentary review of official sources. The results indicate that most establishments implement CSR practices related to responsible waste management, community support, and the promotion of traditional cuisine. However, there is limited strategic planning, insufficient knowledge of CSR, and a lack of formal training in sustainability. The study concludes that CSR is a key factor in improving the sector’s competitiveness and strengthening Portoviejo’s tourism image, and proposes guidelines to build capacity and foster collaborative partnerships among local stakeholders.